The Usage Of Government Formulary For BPJS Inpatients With Ischemic Stroke In Indonesia - Lukman Prayitno; Novita Novita; Sonya Esther; Erlina Puspitaloka Mahadewi (International Journal of Health and Pharmaceutical (IJHP), 2024)
Introduction: Ischemic stroke patients tend to use some medicine. In National Health Security (JKN), the government has created a government formulary as quality control and cost control. The study aims to determine the percentage of government formulary in Hospitals and the affected factors. Method: It was cross sectional quantitative research. It used retrospective data from medical record and prescription of ischemic stroke inpatients from January to June 2019. The data collected include hospital characteristics, patient characteristics, supporting characteristics and treatment costs. Result: The data cames from 17 hospitals. Based on the inclusion and exclusion criteria, 257 medical records were analyzed. The average percentage of drug use was 73.22%. Its was influenced by the hospital class, the number of supporting examinations, the number of drug items. Type B and C hospitals used non government formulary. There were citicolin, mecobalamin, piracetam, neurotropic multivitamin, flunarizine. Conclusion: The average percentage of drug use was still less than 100%. There were still non government formulary drugs used for the therapy of inpatient ischemic stroke. The use of non government formulary drugs was influenced by the hospital class, the number of supporting examinations, the number of drug items.